Cancer Screening of Renal Transplant Patients Undergoing Long-Term Immunosuppressive Therapy - ATA, PINAR (ELSEVIER SCIENCE INC, 2015)
Objective. With this study we aimed to research the effects of immunosuppressive drugs, their cumulative doses, and viral infections on development of malign tumors in patients who have undergone treatment for 5 years. Methods. We examined 100 patients who underwent renal transplantation from 2004 to 2009. Patients had mycophenolate mofetil and steroid in addition to cyclosporine, sirolimus, or tacrolimus as immunosuppressive treatment. For malignancy screening, physical examination, radiologic and endoscopic screening were done, and immunosuppressive drugs and their cumulative doses, age, sex, body mass index (BMI), dialysis history, and viral infection history were investigated. Results. The mean age of patients was 42.03 +/- 11.30 years. There were 1 colon cancer patient, 1 retroperitoneal liposarcoma, 1 renal oncocytoma, 3 Kaposi sarcoma patients treated with cyclosporine; in those treated with Tac there were 1 basal cell carcinoma, 1 Kaposi sarcoma, 2 thyroid carcinoma, 1 breast carcinoma, 1 bladder carcinoma, 1 renal cell carcinoma, and 1 colon carcinoma patients. The mean age of patients having carcinoma was statistically significant compared with those without cancer (P < .01). The prednisolone cumulative dose was significantly higher in carcinoma patients than in patients without carcinoma (P < .01). Results. The use of long-term chronic immunosuppressive therapy may increase the development of cancer. The risk of carcinoma increases with increasing drug dose and time period of the immunosuppressive drug. There was not a negative effect on cancer prevalence in patients with cyclosporine or tacrolimus. But the cumulative dose of steroids significantly increased malignancy occurence.
Keywords: ENDOTHELIAL GROWTH-FACTOR; KIDNEY-TRANSPLANTATION; ORGAN-TRANSPLANTATION; LYMPHOPROLIFERATIVE DISORDERS; MALIGNANCY; SIROLIMUS; RISK; RECIPIENTS; INFECTION; DISEASE